2014
DOI: 10.1186/1471-2164-15-264
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mapping algorithms used in high-throughput sequencing: application to Ion Torrent data

Abstract: BackgroundThe rapid evolution in high-throughput sequencing (HTS) technologies has opened up new perspectives in several research fields and led to the production of large volumes of sequence data. A fundamental step in HTS data analysis is the mapping of reads onto reference sequences. Choosing a suitable mapper for a given technology and a given application is a subtle task because of the difficulty of evaluating mapping algorithms.ResultsIn this paper, we present a benchmark procedure to compare mapping alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 25 publications
2
87
0
Order By: Relevance
“…Tools have been specifically designed to manipulate SAM/BAM files (for example, to quickly sort, merge or retrieve alignments), including the widely used SAMtools (Li et al, 2009b) and Picard. Several benchmarking studies have empirically compared short read alignment methods with respect to various metrics (that is, runtime, sensitivity and accuracy) using both simulated and real data sets from different organisms (Holtgrewe et al, 2011;Ruffalo et al, 2011;Fonseca et al, 2012;Lindner and Friedel, 2012;Schbath et al, 2012;Hatem et al, 2013;Caboche et al, 2014;Shang et al, 2014;Highnam et al, 2015). These analyses demonstrated that results depend strongly on the properties of the input data, and thus there is no single method best suited for all scenarios.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Tools have been specifically designed to manipulate SAM/BAM files (for example, to quickly sort, merge or retrieve alignments), including the widely used SAMtools (Li et al, 2009b) and Picard. Several benchmarking studies have empirically compared short read alignment methods with respect to various metrics (that is, runtime, sensitivity and accuracy) using both simulated and real data sets from different organisms (Holtgrewe et al, 2011;Ruffalo et al, 2011;Fonseca et al, 2012;Lindner and Friedel, 2012;Schbath et al, 2012;Hatem et al, 2013;Caboche et al, 2014;Shang et al, 2014;Highnam et al, 2015). These analyses demonstrated that results depend strongly on the properties of the input data, and thus there is no single method best suited for all scenarios.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Thus, simulation is used to evaluate performance of bioinformatics tools [227,228], design sequencing projects [229] and computational tools [230]. It is also very useful for evaluating of assemblies [231], gene prediction [232], and genotyping and haplotype reconstruction [154,233].…”
Section: Ngs Error Models and Simulationsmentioning
confidence: 99%
“…Additionally, assessment of whether or not an appropriate depth of coverage has been achieved for sequencing should be conducted. Low coverage can lead to false-negative variant calls, while excessive coverage is wasteful and can lead to performance issues such as longer running time or higher memory usage (76). A read coverage of at least 50ϫ has been recommended for the best results (37, 81).…”
Section: Secondary Analysis Reference Mapping and Variant Callingmentioning
confidence: 99%
“…The aligned reads are further processed in a subsequent variant calling stage, which examines the pileup and produces a list of identified variants often stored in a variant call format (VCF) or binary version (BCF) file (73,74). Table 4 provides a sample of popular software used for reference mapping and variant calling, and readers are encouraged to refer to additional reviews (75,76) for more details.…”
Section: Secondary Analysis Reference Mapping and Variant Callingmentioning
confidence: 99%
See 1 more Smart Citation